Incidence of lung cancer among cobalt-exposed women - Tüchsen, Finn; Jensen, M. V.; Villadsen, Ebbe; Lynge, Elsebeth (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVES ': 'The purpose of this study was to estimate the risk of lung cancer for women occupationally exposed to cobalt-aluminate spinel.' ' METHODS ': 'A retrospective cohort of 874 women occupationally exposed to cobalt in two Danish porcelain factories and 520 women not exposed to cobalt were identified from personnel files. Vital status was assessed in the national population register, and incident cancer cases were traced in the national cancer register. Thirteen women (0.92%) were lost to follow-up. The observed deaths and incident cancer cases were compared with the expected number based on rates for all Danish women.' ' RESULTS ': 'The total mortality of the cohort was the same as for all Danish women. The incidence of all cancer was slightly elevated among the exposed women (67 observed, 55.8 expected) and equal to the expected in the reference group (60 observed, 60.6 expected). An increased lung cancer incidence was found both in the exposed group [8 cases, standardized incidence rate (SIR) 2.35, 95% confidence interval (95% CI) 1.01–4.6] and in the reference group (7 cases, SIR 1.99, 95% CI 0.8–4.1). The exposed group had a relative risk ratio of 1.2 (95% CI 0.4–3.8) when compared with the reference group.' ' CONCLUSIONS ': 'Both the cobalt-exposed group and the reference group had an increased lung cancer risk compared with all Danish women, but the risk was only slightly higher for the exposed group than for the reference group. The study was based on few persons, and we recommend a follow-up after five years.
Keywords: cancer; cobalt-aluminate spinel; cohort study; epidemiology